An analysis of nazir, ulama and scholars' understanding of waqf istibdal in Aceh Tengah. - Depi Yanti, Rika; Nurdin, Ridwan (Universitas Syiah Kuala, 2025)
This research aims to analyze the understanding of nazir, ulama and scholars towards istibdal waqf in Aceh Tengah. This research uses a qualitative approach with descriptive method. Data collection was conducted by interviewing five samples/informants, namely three nazir, one ulama and one scholar in Aceh Tengah using accidental sampling technique. The understanding of nazir, ulama and scholars is measured using five indicators of understanding, namely understanding the definition, usefulness, use, role of waqf agencies, and implementation of waqf istibdal. based on the results of this study, the majority of nazir, ulama and scholars in Aceh Tengah understand about waqf istibdal and other general issues and the positive influence of government policies related to waqf istibdal by paying attention to several provisions in accordance with Islamic law.